Bibliothekarisches Grundwissen - Gantert, Klaus (De Gruyter Saur, 2016)
"The 9th edition of this well-known standard textbook has been completely revised. It describes the working steps of acquisition, cataloguing, inventory maintenance, and utilization with an emphasis on new developments and technologies. The new edition presents an up-to-date and comprehensive overview of all aspects of library science, the work of the librarian, and library information services"--